Programmed cell senescence: Role of IL-6 in the pituitary - Sapochnik, Melanie Denise (2017)
IL-6 is a pleiotropic cytokine with multiple pathophysiological functions. As a key factor of the senescence secretome, it can not only promote tumorigenesis and cell proliferation but also exert tumor suppressive functions, depending on the cellular context. IL-6, as do other cytokines, plays important roles in the function, growth and neuroendocrine responses of the anterior pituitary gland. The multiple actions of IL-6 on normal and adenomatous pituitary function, cell proliferation, angiogenesis and extracellular matrix remodeling indicate its importance in the regulation of the anterior pituitary. Pituitary tumors are mostly benign adenomas with low mitotic index and rarely became malignant. Premature senescence occurs in slow-growing benign tumors, like pituitary adenomas. The dual role of IL-6 in senescence and tumorigenesis is well represented in pituitary tumor development, as it has been demonstrated that effects of paracrine IL-6 may allow initial pituitary cell growth, whereas autocrine IL-6 in the same tumor triggers senescence and restrains aggressive growth and malignant transformation. IL-6 is instrumental in promotion and maintenance of the senescence program in pituitary adenomas.